2017
DOI: 10.3748/wjg.v23.i8.1397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking habit on surgical outcomes in non-B non-C patients with curative resection for hepatocellular carcinoma

Abstract: AIMTo analyzed the correlation between smoking status and surgical outcomes in patients with non-B non-C hepatocellular carcinoma (NBNC-HCC), and we investigated the patients’ clinicopathological characteristics according to smoking status.METHODSWe retrospectively analyzed the consecutive cases of 83 NBNC-HCC patients who underwent curative surgical treatment for the primary lesion at Saga University Hospital between 1984 and December 2012. We collected information about possibly carcinogenic factors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…HCC is the main cause of cancer-associated mortality (8,20). It is not easy to make an early diagnosis as there are no obvious symptoms in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is the main cause of cancer-associated mortality (8,20). It is not easy to make an early diagnosis as there are no obvious symptoms in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast in hepatocellular carcinoma patients without viral hepatitis, neither Shih et al [81] nor Kolly et al [80] found any association between smoking and survival outcomes. However, Kai et al [79] did find that current smokers had poorer overall and liver cancer specific survival compared to never smokers and former smokers, respectively, in a cohort of hepatocellular carcinoma patients without hepatitis. Importantly all results adjusted for important confounders such as age, obesity, tumour size/stage and alcohol history, suggesting the results are unlikely to be substantially influenced by confounding.…”
Section: Liver Cancer Smoking and Survival In Liver Cancer Patientsmentioning
confidence: 94%
“…Only 3 studies [79][80][81] identified assessed the association between smoking and survival amongst liver cancer patients (Supplementary table 3).…”
Section: Liver Cancer Smoking and Survival In Liver Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who had smoked >100 cigarettes in their lifetime were considered “smoker”, and all others were considered “non-smoker” [ 32 ]. “Drinker” was defined as a daily ethanol intake > 40 g for men and > 20 g for women [ 33 ]. Additionally, the mean doses to the oral cavity, larynx, skin and 4mm under the skin (skin 4mm ) in the radiotherapy plans were also collected.…”
Section: Methodsmentioning
confidence: 99%